The Potential of Dutch Eggplant (Solanum betaceum) as a Protector of Bcl-2 Expression in the Hearts of Mice (Mus musculus) Exposed to Lead Acetate - Muhammad Hatif Isfahani; Reny I'tishom; I Ketut Alit Utamayasa; Kusuma Eko Purwantari (Green Publisher Indonesia, 2026)
Cardiovascular disease resulting from atherosclerosis, which is triggered by oxidative stress, can result from lead exposure in the body, as this increases the production of reactive oxygen species (ROS). This study aimed to prove the potential of tamarillo (Solanum betaceum) as a protector of Bcl-2 expression in the hearts of mice exposed to lead acetate. This study employed a true experimental laboratory design using stored raw materials (BBT) consisting of male mouse (Mus musculus) hearts, with a completely randomized design (CRD). A total of 40 BBT samples were divided into 5 treatment groups, with each group containing 8 samples. Significant results (p<0.05) were obtained in each treatment group, with the highest Bcl-2 expression found in the group exposed to lead acetate alone, and the lowest Bcl-2 expression found in the group given the highest dose of tamarillo extract. The dosage of tamarillo extract had an inversely proportional effect on the level of Bcl-2 expression in the hearts of mice. The hearts of mice exposed to lead acetate alone (K2) had a median value of 32.97, while the hearts of mice dosed with 400 mg/kg BW/day (P3) had a median value of 5.97.